The Correlation Between Students’ Ability in Grammar and Vocabulary With Students’ Writing Paragraph Achievements at the Eighth Grade MTs Negeri 4 Mandailing Natal - Megasari; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
Abstract This research was intended to find out the correlation between students’ ability in grammar and vocabulary with students’ writing paragraph achievements. There was a correlation between students’ ability in grammar and vocabulary with students’ writing paragraph achievements. From the calculation above it found that tobserved = 5.754whereas the ttable Keyword: grammar ability, vocabulary ability. Writing paragraph achievement = 2.009. It shows that correlation between students’ ability in grammar and vocabulary with students’ writing paragraph achievements was significant at 0.05. From the result, the researcher found that there was correlation of the students’ ability in grammar and vocabulary with students’ writing paragraph achievements. This means that the correlation of the students’ ability in grammar and vocabulary with students’ writing paragraph achievements.